Depressive symptoms and adherence to treatment among people with type 2 diabetes mellitus - Juciene Matos Braz; Mônica Rodrigues Silva; Cristiane Franca Lisboa Gois; Tércio Matos Braz; Valmira dos Santos; Lausimary Araújo São Mateus Silva (Rev Rene)
This study aimed to verify the association between depressive symptoms and socio-demographic and clinical variables, and the adherence to drug treatment among people with type 2 diabetes mellitus (DM2). A descriptive study developed with a sample of 145 people with DM2. We used the Beck Depression Inventory (BDI) and the Measurement of Treatment Adherence (MTA). The average age of participants was 60.4 years, 77.2% were female and 51.7% had a partner. The average BDI was 18.4 and 33.1% of the subjects presented depressive symptoms. Physical activity practice was associated to better BDI evaluation (p<0.05). No important clinically correlation was observed between the BDI and the MTA (r<0.30). Approximately half of the participants tended to trigger depression. Physical activity practice is related to better median values at the BDI.